Systematic survey of plant LTR-retrotransposons elucidates phylogenetic relationships of their polyprotein domains and provides a reference for element classification - Pavel Neumann; Petr Novák; Nina Hoštáková; Jiří Macas (Mobile DNA, 2019)
Abstract Background Plant LTR-retrotransposons are classified into two superfamilies, Ty1/copia and Ty3/gypsy. They are further divided into an enormous number of families which are, due to the high diversity of their nucleotide sequences, usually specific to a single or a group of closely related species. Previous attempts to group these families into broader categories reflecting their phylogenetic relationships were limited either to analyzing a narrow range of plant species or to analyzing a small numbers of elements. Furthermore, there is no reference database that allows for similarity based classification of LTR-retrotransposons. Results We have assembled a database of retrotransposon encoded polyprotein domains sequences extracted from 5410 Ty1/copia elements and 8453 Ty3/gypsy elements sampled from 80 species representing major groups of green plants (Viridiplantae). Phylogenetic analysis of the three most conserved polyprotein domains (RT, RH and INT) led to dividing Ty1/copia and Ty3/gypsy retrotransposons into 16 and 14 lineages respectively. We also characterized various features of LTR-retrotransposon sequences including additional polyprotein domains, extra open reading frames and primer binding sites, and found that the occurrence and/or type of these features correlates with phylogenies inferred from the three protein domains. Conclusions We have established an improved classification system applicable to LTR-retrotransposons from a wide range of plant species. This system reflects phylogenetic relationships as well as distinct sequence and structural features of the elements. A comprehensive database of retrotransposon protein domains (REXdb) that reflects this classification provides a reference for efficient and unified annotation of LTR-retrotransposons in plant genomes. Access to REXdb related tools is implemented in the RepeatExplorer web server (https://repeatexplorer-elixir.cerit-sc.cz/) or using a standalone version of REXdb that can be downloaded seaparately from RepeatExplorer web page (http://repeatexplorer.org/).